النظام القانوني للمهنة الصحفية في الجزائر - حرابي, علاء الدين (جامعة الوادي university el-oued)
أصبح واضحا الاهتمام الكبير الذي توليه مختلف الأنظمة القانونية لقطاع الإعلام عموما ولتنظيم المهنة الصحفية خصوصا، وذلك للدور الكبير والتأثير الذي تلعبه هذه المهنة في وقتنا الحالي على جميع الأصعدة: السياسية، الإقتصادية، الاجتماعية والثقافية، والجزائر كغيرها من الدول ترمي جاهدة منذ الاستقلال وإلى غاية يومنا هذا لبناء دولة قوية، من خلال تبني سياسات إصلاحية مستوحاة من التجارب الأجنبية من أجل تكريس مبدأ الديمقراطية من خلال عدة قوانين إعلامية، واهتمام المشرع الجزائري بتنظيم المهنة الصحفية من شأنه أن يبرز العديد من الحريات المختلفة، فمن خلالها يُمحى ذلك الكبت والقمع الذي مارسته بعض الأنظمة القديمة ولا زالت تمارسه البعض حاليا، وتفسح المجال للتعبير بكل مصداقية عما يدور في المجتمع وهذا ما يعد نقطة انطلاق نحو الإصلاح والتغيير.It has become clear the great interest that the various legal systems of the media sector in general and the organization of the journalistic profession in particular, because of the great role and influence that this profession plays today at all levels: political, economic, social and cultural, and Algeria like other States have been striving since independence and to this day to build a strong state, through the adoption of reform policies inspired by foreign experiences in order to enshrine the principle of democracy through several media laws, and the interest of the Algerian legislature in organizing the journalistic profession would highlight many freedoms , Through which the repression and oppression practiced by some old regimes are erased and still practised by some, and allow for a credible expression of what is going on in society, which is a starting point for reform and change.
م.س.ع.19
Keywords: النظام القانوني، المهنة الصحفية، قوانين الإعلام، علاء الدين حرابي، المشرع الجزائري.; legal system, journalistic profession,AlaaDin Harabi, media laws, Algerian legislature.